Insuficiencia respiratoria aguda en paciente de sexo femenino de 86 años de edad con antecedentes de hipertensión arterial. - Ruiz Hinostroza, Joselyn Andrea (2020)
This clinical case is based on acute respiratory failure in which it is considered the inability of the respiratory system to conserve gas exchange, and thus have adequate arterial oxygen and carbon dioxide levels for the demands of cellular metabolism. This is one of the most frequent causes of morbidity, which is a gateway to the emergency room in hospital care transferred to the intensive care area. Through the application of the respiratory therapy care process with the evaluation of the patient's history and examinations to diagnose and have an exact diagnosis and also all its methods, processes and therapeutic treatment such as non-invasive mechanical ventilation, to improve as well its symptomatological picture and signs that occurs in acute respiratory failure. This case was investigated with the purpose of showing the respiratory therapy care process with the necessary care to obtain favorable progress and efficacy in the 86-year-old patient in the intensive care area of the Luis Vernaza Hospital with acute respiratory failure.